ROLE OF THE ECCLESIASTICAL EDUCATIONAL INSTITUTIONS IN LIFE AND ACTIVITY OF MYROSLAV ANTONOVYCH - Karas’, H. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article elucidates role of the ecclesiastical educational institutions in life and activity of famous Ukrainian conductor and music expert Myroslav Antonovych. The author concentrates at his work in Lviv Junior Ecclesiastical Seminary (1933-1939) and Ukrainian Catholic Ecclesiastical Seminary in Hirshberg (Bavaria) – Culemborg (Netherlands,1947–1950) namely – chorus conduction, teaching of liturgy singing and theory of vocal music.